Perancangan Sisitem Informasi Akademik Berbasis Website dengan Database MySQL pada Sekolah - Gumanti, Miswan; Kusumawati, Tini Damara Nurul; Anwar, Mohammad Saiful; Assidiqi, Euis Zulfa; Wazaki, Wahyu (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to design and implement a web-based academic information system connected to a database, to improve management efficiency, information accuracy, and academic data precision. This study applies the Waterfall system development model, which includes the stages of requirement analysis, design, implementation, and testing. The system is developed using the PHP programming language with MySQL as the database. To ensure that each function operates according to user requirements, the testing phase is conducted using the Black Box Testing method. The results of the study indicate that the developed system is capable of integrating all academic data into a single centralized database, making data management and retrieval faster and more accurate, while also reducing recording errors that frequently occurred previously. Based on the test results and evaluations conducted by users, the web-based academic information system designed shows the ability to improve the effectiveness of school administration performance. Therefore, the implementation of this system at SMK Yapemi Pagelaran is considered feasible and relevant as a solution to support more systematic, accurate, and easily accessible academic data management.